Clubbing and hypertrophic osteoarthropathy: insights in diagnosis, pathophysiology, and clinical significance. Issue 3 (3rd May 2016) - Callemeyn, Jasper; Van Haecke, Peter; Peetermans, Willy E.; Blockmans, Daniel
Abstract : Background : Digital clubbing and hypertrophic osteoarthropathy (HOA) form a diagnostic challenge. Subtle presentations of clubbing are often missed. The underlying pathophysiology remains unclear. Establishing a differential diagnosis based on nonspecific signs can be cumbersome. Finally, the prognostic value of clubbing and HOA remains unclear. Objective: This article reviews clinical criteria and pathophysiology of clubbing and HOA. A diagnostic algorithm is proposed, based on etiology and current insights. The prognostic impact on associated diseases is discussed. Methods: The Internet databases Medline and Embase were searched. Articles were selected based on relevance of abstract, article type and impact of the journal. Results: Diagnostic criteria include Lovibond's profile sign, distal/interphalangeal depth ratio and Schamroth's sign. Three pathophysiological causes of clubbing can be distinguished: hypoxia, chronic inflammation and aberrant vascularization. A prominent role for vascular endothelial growth factor is suggested. Associated symptoms and clinical signs should guide the initial diagnostic evaluation. Finally, clubbing is a negative prognostic factor in certain pulmonary disorders, including cystic fibrosis.